The Persistence of Self-Employment Across Borders: New Evidence on Legal Immigrants to the United States - Randall Kekoa Quinones Akee; David A. Jaeger; Konstantinos Tatsiramos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
Using recently-available data from the New Immigrant Survey, we find that previous self-employment experience in an immigrant's country of origin is an important determinant of their self-employment status in the U.S., increasing the probability of being self-employed by about 7 percent. Our results improve on the previous literature by measuring home-country self-employment directly rather than relying on proxy measures. We find little evidence to suggest that home-country selfemployment has a significant effect on U.S. wages in either paid employment or self employment.
Keywords: J61; J21; 330; Self-employment; entrepreneurship; New Immigrant Survey